2010
DOI: 10.1029/2010gl042873
|View full text |Cite
|
Sign up to set email alerts
|

Intermodel variability of the poleward shift of the austral jet stream in the CMIP3 integrations linked to biases in 20th century climatology

Abstract: [1] Future climate predictions by global circulation models in the Coupled Model Intercomparison Project Phase 3 (CMIP3) archive indicate that the recent poleward shift of the eddy-driven jet streams will continue throughout the 21st century. Here it is shown that differences in the projected magnitude of the trend in the Southern Hemisphere are well correlated with biases in the latitude of the jet in the simulation of 20th century climate. Furthermore, the latitude of the jet in the models' 20th century clim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

28
291
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 230 publications
(321 citation statements)
references
References 20 publications
28
291
2
Order By: Relevance
“…[23] There is a strong relationship between the latitude of the jet and the time scale of the leading mode of variability, or the so called annular modes [Kidston and Gerber, 2010]. A number of authors [Gerber and Vallis, 2007; have argued that the persistence of zonal index and the annular modes is due to the self-maintenance of eddydriven jets.…”
Section: Discussionmentioning
confidence: 99%
“…[23] There is a strong relationship between the latitude of the jet and the time scale of the leading mode of variability, or the so called annular modes [Kidston and Gerber, 2010]. A number of authors [Gerber and Vallis, 2007; have argued that the persistence of zonal index and the annular modes is due to the self-maintenance of eddydriven jets.…”
Section: Discussionmentioning
confidence: 99%
“…Increases in global-mean surface temperature can explain up to 79 % of the total inter-model variation in tropical expansion, noteworthy because it occurs within the inter-model space of fully coupled climate models. Different mean states (Kidston and Gerber, 2010), the representation of parameterized processes (Frierson, 2007), the strength of cloud feedbacks (Feldl and Bordoni, 2016), and model design choices such as horizontal resolution (Landu et al, 2014;Lorant and Royer, 2001;Davis and Birner, 2016) can all influence the circulation and its response. Tropical belt width changes are thus part and parcel of global climate change.…”
Section: Discussionmentioning
confidence: 99%
“…In the following subsections, we will focus on the magnitude increase of EKE from the perspectives of the low-level static stability and its historical mean state. [Kidston and Gerber, 2010] and current CMIP5 [Barnes and Polvani, 2013] found that the future response of jet location is strongly related to its historical position. Similarly, the relationship between ΔEKE and the historical intensity of EKE, ΔEKE versus EKE, is then examined (Figure 2b).…”
Section: Resultsmentioning
confidence: 99%
“…Similar with the relationship between poleward shift of jet and its historical location [Kidston and Gerber, 2010], the correlation between ΔEKE and EKE can be interpreted in the term of model internal mechanisms. Since the historical EKE is underestimated in CMIP5 models, the strong enhancement of EKE in future warming climate is favorable to happen in the model with weak EKE.…”
Section: 1002/2015gl064641mentioning
confidence: 99%
See 1 more Smart Citation